Optimization of COD, nitrate-N and phosphorus removal from hatchery wastewater with acclimatized mixed culture - Norazwina, Zainol; Kamaliah, Abdul Samad; Che Asilah Ilyana, Che Jazlan; Nurul Ain, Razahazizi (Elsevier Ltd, 2022)
The goal of this study is to optimize the condition of the pollutant removal process by using acclimatized mixed culture (AMC) in the treatment of contaminated waste from the hatchery industry. The removal of chemical oxygen demand (COD), nitrate-N, and total phosphorus was optimized using a central composite design and the Response Surface Methodology (RSM) with two parameters: AMC content and retention time (days). Each factor had a range value of 15%–35% AMC content and a retention time of 3–5 days, with COD, nitrate-N, and total phosphorus removal as responses. Prior to experimentation, the synthetic wastewater was prepared, and the mixed cultures were acclimatized. In 13 runs, the experiment was carried out in accordance with the setup created by the Design-Expert software. The sample was tested for COD, nitrate-N, and total phosphorus using a Hach spectrophotometer. The findings show a strong relationship between predicted and experimental COD, nitrate-N, and total phosphorus removal values. At optimum conditions of 29% AMC content and 4 days of retention time, removal of COD, nitrate-N, and total phosphorus was observed to be 28%, 80% and 36%, respectively. The discovery also revealed that maximum values of removal of 62% COD, 94% nitrate-N, and 46% total phosphorus could be obtained under various optimum conditions. The study shows that, the acclimatized mixed culture (AMC) can be used as a potential biological wastewater treatment as well as a natural removal of COD, nitrate-N, and total phosphorus.